Konfiks Derivasi Per-/-an dalam Debat Capres-Cawapres Tahun 2024: Metode Linguistik Korpus - Dhika JR, Vicno Triwira (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2024)
This research aimed to discuss the “per-/-an” confix which has undergone derivation in Indonesian. This research used the presidential and vice presidential candidate debate script number 01 as the research object studied. This research used a qualitative corpus linguistics approach. The corpus linguistic approach used in this research utilized the KORTARA (Korpus Nusantara) corpus linguistic application. The KORTARA corpus linguistic application (Korpus Nusantara) is an application that can help to collect, process and analyze linguistic data digitally. Data collection in this research utilized the affix word search feature to find specific data containing affixes. The affix word search feature was lasted by accessing the corpus menu in the KORTARA (Korpus Nusantara) application, then selecting the 2024 presidential-cawapres debate script as the object for research. Based on the research that has been carried out, 56 data were obtained on the use of the derivation confix per-/-an in the corpus of the 01 Presidential-Cawapres debate texts in 2024. The results of this research can have implications in the scientific field of morphology related to the principles of derivational development in Indonesian.